Influence of different factors on momentum transfer in mechanically agitated multiphase systems - Cudak Magdalena; Kiełbus-Rąpała Anna; Major-Godlewska Marta; Karcz Joanna (Chemical and Process Engineering)
A comparative analysis concerning the influence of different factors on momentum transfer in mechanically agitated systems was carried out on the basis of experimental results for solid-liquid, gas-liquid and gas-solid-liquid systems. The effects of the impeller - baffles system geometry, scale of the agitated vessel, type and number of impellers and their off-bottom clearance, as well as physical properties of the multiphase systems on the critical impeller speeds needed to produce suspension or dispersion, power consumption and gas hold-up were analysed and evaluated.